Defective running shoes as a contributing factor in plantar fasciitis in a triathlete - Wilk, B. R.; Fisher, K. L.; Gutierrez, W. (Journal of Orthopaedic & Sports Physical Therapy, 2000)
Abstract: Study Design: Case study of a patient who developed plantar fasciitis after completing a triathlon. Objectives: To describe the factors contributing to the injury, describe the rehabilitation process, including the analysis of defective athletic shoe construction, and report the clinical outcome. Background: Plantar fasciitis has been found to be a common overuse injury in runners. Studies that describe causative factors of this syndrome have not documented the possible influence of faulty athletic shoe construction on the symptoms of plantar fasciitis. Methods and Measures: The patient was a 40-year-old male triathlete who was followed up for an initial evaluation and at weekly intervals up to discharge 4 weeks after injury and at 1 month following discharge. Perceived heel pain, ankle strength, and range of motion were the primary outcome measures. Shoe construction was evaluated to assess the integrity of shoe manufacture and wear of materials by visual inspection of how shoe parts were glued together, if shoe parts were assembled with proper relationship to each other, if the shoe sole was level when resting on a level surface, and if the sole allowed unstable motion. Results: The patient appeared to have a classic case of plantar fasciitis with a primary symptom of heel pain at the calcaneal origin of the plantar fascia. On initial evaluation, right heel pain was a 9 of 10, plantar flexion strength was a 3+/5, and ankle dorsiflexion motion was 10°. One month after discharge, perceived heel pain was 0, plantar flexion strength was 5/5, and dorsiflexion motion was 15° and equal to the uninvolved extremity. The right running shoe construction deficit was a heel counter that was glued into the shoe at an inward leaning angle, resulting in a greater medial tilt of the heel counter compared with the left shoe. The patient was taught how to examine the integrity of shoe manufacture and purchased a new pair of sound running shoes. Conclusions: A running shoe manufacturing defect was found that possibly contributed to the development of plantar fasciitis. Assessing athletic shoe construction may prevent lower extremity overuse injuries.